PFHub: The Phase-Field Community Hub. Issue 1 (24th September 2019) - Wheeler, Daniel; Keller, Trevor; DeWitt, Stephen J.; Jokisaari, Andrea M.; Schwen, Daniel; Guyer, Jonathan E.; Aagesen, Larry K.; Heinonen, Olle G.; Tonks, Michael R.; Voorhees, Peter W.; Warren, James A.
Scientific communities struggle with the challenge of effectively and efficiently sharing content and data. An online portal provides a valuable space for scientific communities to discuss challenges and collate scientific results. Examples of such portals include the Micromagnetic Modeling Group (μMAG) [1 ], the Interatomic Potentials Repository (IPR) [2 3 ] and on a larger scale the NIH Genetic Sequence Database (GenBank) [4 ]. In this work, we present a description of a generic web portal that leverages existing online services to provide a framework that may be adopted by other small scientific communities. The first deployment of the PFHub framework supports phase-field practitioners and code developers participating in an effort to improve quality assurance for phase-field codes.